Preliminary Characterization of Cervical Microflora in Pregnant Women with Cervical Incompetence - Jiang JW; Rong Y; Fu JR; Meng YC; Lu D (International Journal of Women's Health)
Jing-Wen Jiang,* Yun Rong,* Jing-Ran Fu, Yan-Cen Meng, Dan Lu Department of Obstetric and Gynecology, Shijiazhuang Fourth Hospital, Shijiazhuang, Hebei Province, 050000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing-Wen Jiang, Department of Obstetric and Gynecology, Shijiazhuang Fourth Hospital, No. 91 of Xueyuan Road, Yuhua District, Shijiazhuang, Hebei Province, 050000, People’s Republic of China, Tel +8617733998766, Email jingwenjiang0@outlook.comObjective: The objective of this study was to investigate the impact of cervical microflora on cervical function and the efficacy of cervical cerclage in restoring the normal microecology of the reproductive tract, thereby improving pregnancy outcomes.Methods: Based on defined inclusion and exclusion criteria, six pregnant women who underwent cervical cerclage for cervical incompetence at Shijiazhuang No. 4 hospital between January and May 2024 were enrolled. Cervical secretions were collected from each participant both prior to the procedure and one month afterward. High-throughput sequencing (Illumina MiSeq) was used to analyze the diversity and community structure of cervical microflora, enabling the assessment of changes associated with the cervical cerclage procedure.Results: In this study, the composition of two groups of samples was analyzed at the “genus” level. Lactobacillus spp. predominated both pre- and post-operative samples. In the postoperative period, there was a decrease in the relative abundance of Gemella, Rhodococcus, and Anaerococcus, while an increase in the relative abundance of Bifidobacterium was noted. When the composition of the flora of two groups of samples was analyzed at the “phylum” level, the top four dominant bacteria with the highest abundance were Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes, with Firmicutes being the most abundant, and there was no significant difference between the two groups. However, there was a gradual increase in the abundance of Actinobacteria and a decrease in Proteobacteria and Bacteroides over time.Conclusion: The results of this study are useful in exploring the effect of cervical flora on outcomes in cervical cerclage, potentially contributing to accelerating the restoration of normal vaginal microecology and improving pregnancy outcomes.Keywords: cerclage, cervical incompetence, flora variability, Illumina MiSeq, microecology